Pusa Hybrid-4: First gynoecious based high yielding hybrid of bitter gourd for commercial cultivation - Behera, T K (Indian Horticulture, 2022)
Bitter gourd is an economically important multipurpose vegetable and highly valuable for its nutritional contents like carbohydrate, proteins, vitamins, minerals (mainly high concentrations of ascorbic acid and iron) and numerous medicinal uses including treatment for diabetes and also possess anti-microbial, anti-oxidant, and anti-viral activities. Pusa Hybrid-4, the first gynoecious based early and high yielding hybrid, has been released and recommended by the Central Sub- Committee on Crop Standards, Notification and Release of Varieties for Horticultural Crops for cultivation in National Capital Region of Delhi including Delhi and its adjoining areas of Haryana, Rajasthan and Uttar Pradesh.